Fresno County Bar Association Sponsored Fresno Courthouse Historical Display Case - Watkins, Howard::::::::: (1989)
Fresno County Bar Association President G. Dana French and Fresno County Board of Supervisors Chair Vernon Conrad using giant scissors to cut red ribbon